Classification of 17 species Aegilops using DNA barcoding and SNPs, reveals gene flow among Aegilops biuncialis, Aegilops juvenalis, and Aegilops columnaris - Wang, Xiaohan; Yoo, Eunae; Lee, Seungbum; Cho, Gyu-Taek; Lee, Gi-An; Yi, Jung Yoon; Du, Xiaoxuan; Han, Seahee; Hyun, Do Yoon; Ro, Nayoung; Kim, Kyung-Min (Frontiers in Plant Science, 2022)
Rapid changes in agricultural environments caused by global warming pose a major challenge to food production and safety. Common wheat (Triticum aestivum) is a hexaploid plant (AABBDD) that shares large numbers of quantitative traits and resistance genes with B and D genomes of Aegilops species, which are responsible for several metabolic functions and biosynthetic processes, particularly in plant adaptation to biotic as well as abiotic stresses. Comparatively, the abundance of the Aegilops gene pool is much higher than that of Triticum. Therefore, we used four universal DNA barcodes for plants (ITS2, matK, rbcL, and psbM-petN) to construct a phylogenetic tree to classify the genus Aegilops. Fourteen species were distinguished among a total of 17 representative species. Aegilops biuncialis, Aegilops juvenalis, and Aegilops umbellulata could not be grouped into any of the clusters in the phylogenetic tree, indicating that these three species could not be distinguished by four DNA barcodes. Therefore, from 2408 SNPs obtained using genotyping by sequencing (GBS), we manually screened 30 SNPs that could be potentially used to classify these three species. The results of gene flow and genetic differentiation index (Fst) showed that the genetic differentiation among the three species was small, and there was bidirectional horizontal gene transfer between the three species, which was consistent with our results that the three species were difficult to classify by DNA barcode.